A iluminação cênica no trabalho do ator de teatro - Moura, Luiz Renato Gomes (2014)
This research aims to investigate how the stage lighting can be articulated in the creation of theater actor process. To we reach this reflection, it is necessary to understand the space of the rehearsal room, where the actor works as a place where their function receives influences of other artists who are creating the spectacle.Collaborative processes are analyzed three Cia de Teatro Engenharia Cênica: Irremediável, 2007; Doralinas e Marias , 2009; O Menino Fotógrafo, 2011, aiming to understand the collaborative theater potentializes, the intersection and the exchange of experiences in the rehearsal room, collaborating actively for the training of persons involved in creating the show. The research proposes an investigation of how the creative process of stage lighting is gaining ground in the rehearsal room in the language of theater directing, showing mainly how is your "co-evolutionary" creation with the creative process of the actor